ANALYSES OF ORGANIZATION AND MILK PRODUCTION ECONOMICS ON FARMS IN MONTENEGRO - Ćetković, Jasmina; Despotović, Aleksandra; Cimbaljević, Miroslav (Economics of Agriculture, 2012)
This document presents analyses of organization and milk production economics on farms in Montenegrin municipalities: Berane, Niksic and Pljevlja. In first part of this document are analyzed basic aspects of production organization on observed farms. In second part based on empirical research is given analyze of milk production economics on observed farms. By this analyze are determined total production costs per cattle on annual level, value of achieved production per cattle on annual level, as well as cost price of main products on observed farms. Based on previous values some of basic economic parameters are determined such as: ratio of economy on farms in observed areas, share in income per cattle on annual level in observed areas and size of profit per cattle on annual level in observed areas. At the end of this document are given conclusions of conducted research and given recommendation for improvement of current situation.